Educator Practices and Perceptions of Integrating Sustainability and Food Systems Concepts Into Elementary Education: Comparative Case Study in Two Northwestern States in the United States - Stewart, Alyssa L.; Ahmed, Selena; Warne, Teresa; Byker Shanks, Carmen; Arnold, Shannon (Frontiers in Sustainable Food Systems, 2021)
Elementary education can equip future consumers and leaders with the systems thinking skills, real-world experiences, and knowledge to make decisions and lead progress toward sustainability transitions. The implementation of learning standards that focus on sustainability is one approach for integrating sustainability and food systems content into elementary education. The purpose of this study was to administer a survey with elementary-level educators to: (1) identify practices and perceptions of integrating sustainability and food systems concepts into the classroom; and (2) determine if practices and perceptions vary based on the presence of state learning standards focused on sustainability. A total of 171 educators completed the majority of the survey from two northwestern states in the United States: Washington (which has state learning standards focused on sustainability) and Montana (which does not have sustainability learning standards). Findings that 30% or less of the surveyed educators integrate sustainability and food systems content in their classroom highlights the urgent need for reforming elementary school curriculum to integrate sustainability as a central unifying framework to support societal and planetary health. Given the similarities in survey responses between educators in Washington and Montana, findings emphasize that state learning standards focused on sustainability are not adequate on their own to foster teacher adoption of sustainability content. There is thus a need for larger curriculum reformation to integrate sustainability as a framework, development of place-based teacher resources, and open access professional development to ensure that elementary-school students cultivate the systems thinking skills, real world experience, and knowledge that will allow them to develop the competencies to ultimately guide society toward meeting the Sustainable Development Goals of the United Nations.